(untitled) (International Journal of Built Environment and Sustainability, 2016)
The objective of this paper is to examine the role of non-motorized transport (NMT) as green mobility solutions in improving the last mile connectivity (LMC) to mass transit systems. There are evidences of its growing significance, which is established through various international experiences, and case studies. The paper discusses transport policies for Indian cities with respect to LMC, NMT and transit systems and their interface. The paper also presents the empirical findings of a study on NMT usage as first/last mile options for a few metro stations in Delhi, India. It analyses metro user characteristics and choices for the selected stations with a lens on NMT usage for covering the last mile. It is observed that NMT comes out as the most preferred option for covering the first/last mile to transit systems, despite the challenging situations under which NMTs operate. The study further points out that the type of NMT mode availed by commuters varies with varying situational context and depends on locational and user attributes. It is interesting to note that while introduction of “bicycles on hire” worked very well at a particular station, the same had no takers at another. The paper contends that resorting to standard solutions for LMC may not be the right approach; rather it must be based on user and other contextual analysis. The paper concludes with outlining a holistic policy approach that treats NMT planning as a non-negotiable component of transit planning to achieve higher ridership (for the transit operator), better journey experience (for the commuter) and larger sustainability goals.